Effect of cadmium and copper exposure to growth, secondary metabolites and antioxidant activity in a medicinal plant Sambung nyawa (Gynura procumbens) - Ibrahim, Mohd Hafiz; Yap, Chee Kong; Mohd Zain, Nurul Amalina (M D P I AG, 2017)
A randomized complete block (RCBD) study was designed to investigate the effects of cadmium (Cd) and copper (Cu) on the growth, bioaccumulation of the two heavy metals, metabolite content and antibacterial activities in Gyanura procumbens (Lour.) Merr. Nine treatments including (1) control (no Cd and Cu); (2) Cd 2 = cadmium 2 mg/L; (3) Cd 4 = cadmium 4 mg/L; (4) Cu 70 = copper 70 mg/L; (5) Cu 140 = copper 140 mg/L); (6) Cd 2 + Cu 70 = cadmium 2 mg/L + copper 70 mg/L); (7) Cd 2 + Cu 140 = cadmium 2 mg/L + copper 70 mg/L); (8) Cd 4 + Cu 70 = cadmium 4 mg/L+ copper 70 mg/L and (9) Cd 4 + Cu 140 = cadmium 4 mg/L + copper 140 mg/L) were evaluated in this experiment. It was found that the growth parameters (plant dry weight, total leaf area and basal diameter) were reduced with the exposure to increased concentrations of Cd and Cu and further decreased under interaction between Cd and Cu. Production of total phenolics, flavonoids and saponin was observed to be reduced under combined Cd and Cu treatment. The reduction in the production of plant secondary metabolites might be due to lower phenyl alanine lyase (PAL) activity under these conditions. Due to that, the 1,1-diphenyl-2-picrylhydrazyl (DPPH), ferric reducing antioxidant potential (FRAP) and antibacterial activities was also found to be reduced by the combined treatments. The current experiments show that the medicinal properties of G. procumbens are reduced by cadmium and copper contamination. The accumulation of heavy metal also was found to be higher than the safety level recommended by the WHO in the single and combined treatments of Cd and Cu. These results indicate that exposure of G. procumbens to Cd and Cu contaminated soil may potentially harm consumers due to bioaccumulation of metals and reduced efficacy of the herbal product.